Applying computer technologies in electronic devices engineering on example of square wave-form generator creation - A. V. Ponomarev (Омский научный вестник)
The article contains the analysis of computer technologies application for electronic devices designing. There are basic stages of device design on the example of an adjustable square wave-form generator. It contains the description of its operation principles, circuit diagram, features of PCB and shell creation. Acquaintance with design of basic stages on the example of a simple device can help starting design devices for students and young scientist researches.